Use of phytase at graded levels for improving nutrient digestibility, growth and hematology of Catla catla fingerlings fed Moringa oleifera seed meal (MOSM) based diet - Hussain, Syed Makhdoom; Shahzad, Muhammad Mudassar; Aslam, Nosheen; Javid, Arshad; Hussain, Abdullah Ijaz; Hussain, Majid; Arsalan, Muhammad Zubair-ul-Hassan (Indian Journal of Fisheries, 2017)
Present research work was conducted to evaluate the effect of phytase supplementation on nutrient digestibility, growth performance and hematological indices of Catla catla (Hamilton, 1822) fingerlings fed Moringa oleifera seed meal (MOSM) based diet. Existence of phytate in plant byproducts decreases the bioavailability of nutrients to fish, resulting in low nutrients availability, poor fish growth and hematological indices in fish body. Moringa byproducts such as M. oleifera seed meal (MOSM) was used as test ingredient to formulate experimental diet. Experimental diet was divided into six test diets and were supplemented with graded levels (0, 300, 600, 900, 1200 and 1500 FTU kg-1) of phytase. The fingerlings were fed at the rate of 4% of live wet weight twice a day in V-shaped indoor tanks. Phytase supplementation showed significant (p<0.05) improvement in bioavailability of nutrients, growth indices and hematological parameters. Results showed that maximum growth performance, digestibility of nutrients and improved hematological values of C. catla fingerlings were noted at 900 FTU kg-1 level of phytase supplementation in MOSM based test diet. It was concluded that phytase supplementation at 900 FTU kg-1 level was helpful to develop an eco friendly and cost effective fish feed incorparating moringa seed meal.